Alcohol, Trait Anger, and Psychological Flexibility: A Laboratory Investigation of Intimate Partner Violence Perpetration - Grom, Jessica L. (J Contextual Behav Sci, 2021)
The I(3) Model is a meta-theoretical framework that posits intimate partner violence (IPV) perpetration is the product of three interactive factors: instigators, impellors, and inhibitors. The present study examined the effects of trait anger (an impellor), psychological flexibility (a disimpellor), and alcohol intoxication (a disinhibitor) on IPV perpetration. Participants were 249 heavy drinkers (41% female) who had perpetrated IPV toward their current partner in the past year. Participants completed self-report measures of trait anger and psychological flexibility, were randomly assigned to consume an alcoholic or non-alcoholic beverage, and then engaged in the Taylor Aggression Paradigm (Taylor, 1967) ostensibly against their current partner. Analyses detected a small-to-medium effect for two separate two-way interactions. First, a significant Beverage x Psychological Flexibility interaction was detected. Consistent with the I(3) Model, explication analyses revealed that alcohol intoxication predicted higher levels of IPV perpetration in those who reported low, but not high, psychological flexibility (i.e., low disimpellance). Second, although the Beverage x Trait Anger interaction was non-significant, explication analyses revealed that alcohol intoxication predicted higher levels of IPV perpetration among those who reported low, but not high, trait anger (i.e., low impellance). These results have several potential treatment implications among alcohol-consuming clients.